Evaluación de las semillas de “lágrimas de job” (coix lacryma-jobi) para la alimentación de pollos parrilleros; en la granja experimental “bioalimentar” en el sector: Pasa provincia: Tungurahua - Claudio Reinoso, Jeaneth del Rocío (2010)
The chicken production has had an important development during the last years and it is very diffused in our country, mainly in temperate and warm climates, due to its high profitability, good acceptance in the market, easiness to find good lines and concentrated foods of excellent quality that provide very good results in nutritious conversion. The origin of the corral birds is located in the southeast of Asia. The British naturalist Charles Darwin considered them descending of an only wild species, the rooster bankiva that lives in wild state from India to Philippines going by the Asian Southeast. They are granívoros and ovovivíparos, their big and heavy body, as well as their short wings disable most of the varieties for the flight, except at short distances. In the adults of the two sexes the head is adorned with some outgrowths to both sides of the pick and a naked and fleshy crest that it is more prominent in the male and he/she has diverse forms in function of the different lines....